The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13024-016-0114-3
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose upregulates progranulin expression in human and mouse models of GRN haploinsufficiency: a novel therapeutic lead to treat frontotemporal dementia

Abstract: BackgroundProgranulin (PGRN) is a secreted growth factor important for neuronal survival and may do so, in part, by regulating lysosome homeostasis. Mutations in the PGRN gene (GRN) are a common cause of frontotemporal lobar degeneration (FTLD) and lead to disease through PGRN haploinsufficiency. Additionally, complete loss of PGRN in humans leads to neuronal ceroid lipofuscinosis (NCL), a lysosomal storage disease. Importantly, Grn−/− mouse models recapitulate pathogenic lysosomal features of NCL. Further, GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 78 publications
(92 reference statements)
0
68
0
Order By: Relevance
“…For instance, the transcription factor EB (TFEB), a master regulator of autophagy-lysosomal gene expression, is implicated in GRN expression through its specific recognition and binding to E-box consensus sequences ( 5′-CANNTG-3′ ) in the GRN promoter region (Belcastro et al, 2011). Since TFEB overexpression has been shown to be sufficient to enhance GRN mRNA and PGRN protein levels in human cells (Holler et al, 2016), we hypothesized that HDAC inhibitors that affect PGRN expression would have a different effect on TFEB levels than those HDAC inhibitors that do not. Indeed, we observed that the level of this enhancement in TFEB levels correlated with an increase in PGRN in a dose-dependent manner (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the transcription factor EB (TFEB), a master regulator of autophagy-lysosomal gene expression, is implicated in GRN expression through its specific recognition and binding to E-box consensus sequences ( 5′-CANNTG-3′ ) in the GRN promoter region (Belcastro et al, 2011). Since TFEB overexpression has been shown to be sufficient to enhance GRN mRNA and PGRN protein levels in human cells (Holler et al, 2016), we hypothesized that HDAC inhibitors that affect PGRN expression would have a different effect on TFEB levels than those HDAC inhibitors that do not. Indeed, we observed that the level of this enhancement in TFEB levels correlated with an increase in PGRN in a dose-dependent manner (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, stressful stimuli, such as hypoxia, acidosis, hyperosmolarity and inhibition of lysosomal function by artificial alkalinization 52 , seem to increase progranulin production and secretion 72,77,78 , alter its glycosylation 18 and possibly promote its cleavage 12,14,50,51 . Low circulating levels of progranulin in GRN carriers 38 suggest that progranulin expression from the wild-type allele might be a potential therapeutic target.…”
Section: Therapeutics Discoverymentioning
confidence: 99%
“…These types of studies are currently ongoing for a variety of other diseases. Frontotemporal lobar degeneration occurs via haploinsufficiency of the GRN gene, which encodes the protein progranulin (PGRN), and a recent study to screen a library of small molecules identified a naturally-occurring disaccharide, trehalose, as a molecule capable of increasing endogenous PGRN levels [63]. This group confirmed their findings in both an animal model of the disease and in iPSCs that had innate GRN mutations.…”
Section: Clinical Applications: Towards a Treatmentmentioning
confidence: 81%